Correctional oversight bodies’ resources and protections across the European Union: Are their hands tied? - Aizpurua, Eva (Criminology & criminal justice, 2022)
Oversight bodies play a critical role in upholding human rights standards in prison. Several international instruments require states to establish independent forms of prison oversight and to give them the powers they need to conduct their work. Resources are central to the effectiveness and independence of oversight bodies. Of equal importance is the ability of prison oversight bodies to offer protections against reprisals for those who choose to speak to them and for their own staff. In this article, we provide results from the first survey of prison oversight bodies in the European Union and the United Kingdom, focusing on the resources and protections which prison oversight bodies in these states have to enable them to conduct their work. Our results suggest the need to strengthen the financial independence of prison oversight bodies, with slightly less than half of the bodies having their own budget to monitor prisons. Bodies which had their own budgets had a greater number of staff members and a greater variety of professional backgrounds among their members, likely influencing their ability to fulfil their mandate. Our results also point to the need to develop further protection mechanisms against reprisals for those who speak with inspectors as well as for staff from prison oversight bodies.